Ensuring Economic Growth through the Development of Digital Technologies in Uzbekistan - Mirzakarimova Muyassar Muminovna; Narmanov Ulugbek Abdugapparovich (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
Development of the digital economy in the period of the global pandemic is one of the issues of strategic importance for Uzbekistan, like other countries, which determines its world-wide competitiveness, and through this, it shows that it is necessary to address the issues of socio-economic development of the country. The gradual transition to a digital economy in Uzbekistan will help solve many economic and promising problems and ensure economic growth. A number of issues and challenges have been addressed in terms of ensuring economic growth through the development of the digital economy and its economic significance.